Unsur Instrinsik Cerpen "Gubrak" Karya Seno Gumira Ajidarma - Nelsa Siti Nur Lestifiani; Salsadilla Putri Heryana (Kajian Administrasi Publik dan ilmu Komunikasi, 2024)
The short story "Gubrak" by Seno Gumira Ajidarma is an interesting short story to analyze. This research analyzes the intrinsic elements of the short story 'Gubrak' by Seno Gumira Ajidarma which aims to determine the important elements used in the short story 'Gubrak' by Seno Gumira Ajidarma. The problem that will be answered in this research is what elements are in the short story "Gubrak" by Seno Gumira Ajidarma. The aim of this research is to determine the intrinsic elements of short stories. The research method used is a qualitative method because it is descriptive and leads to analysis by presenting an analysis of the intrinsic elements of the short story. The results of this research show that there are elements found in the short story 'Gubrak' by Seno Gumira Ajidarma including theme, characters, plot, setting, point of view, and message. This analysis is useful for finding out what elements are in the short story 'Gubrak' by Seno Gumira Ajidarma. The benefit of this research is that it allows viewers of literary works to feel the emotions contained in the literary work, especially literary works in the form of writing, so that the intrinsic elements can reflect individual expressions and are a means of depicting the atmosphere of the story. And literary works become more beautiful and do not abandon the aesthetic value of a literary work.